2012
DOI: 10.1097/aln.0b013e31825575e6
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of Stored Autologous Blood Does Not Alter Reactive Hyperemia Index in Healthy Volunteers

Abstract: Background Transfusion of human blood stored for over 2 weeks is associated with increased mortality and morbidity. During storage, packed erythrocytes progressively release hemoglobin, which avidly binds nitric oxide. We hypothesized that the nitric oxide mediated hyperemic response following ischemia would be reduced after transfusion of packed erythrocytes stored for 40 days. Methods and results We conducted a cross-over randomized interventional study, enrolling 10 healthy adults. Nine volunteers complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
1
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
(37 reference statements)
4
30
1
1
Order By: Relevance
“…We also exposed the forearm vasculature with a relatively larger transfusion exposure by infusing the blood directly into the brachial artery circulation. Prior studies in humans assessed vascular endothelial function by noninvasive measures of flow-mediated vasodilation after the systemic transfusion of 1 U of packed RBCs (PRBCs) (23,24,31). Transfusion studies in normal volunteers are limited by the amount of RBCs that can be infused.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also exposed the forearm vasculature with a relatively larger transfusion exposure by infusing the blood directly into the brachial artery circulation. Prior studies in humans assessed vascular endothelial function by noninvasive measures of flow-mediated vasodilation after the systemic transfusion of 1 U of packed RBCs (PRBCs) (23,24,31). Transfusion studies in normal volunteers are limited by the amount of RBCs that can be infused.…”
Section: Discussionmentioning
confidence: 99%
“…Berra and colleagues (31) reported that 1-U transfusion of 40-day-aged red cells did not affect the reactive hyperemia index, a noninvasive measure of endothelial function, compared with transfusions of 3-day-aged red cells. In contrast, in a followup study the same group evaluated a single unit transfusion of autologous 40-daystored leukoreduced red cells into subjects with endothelial dysfunction and demonstrated increased post-transfusion levels of CFPHb, NO consumption, and pulmonary artery pressures estimated by Doppler echocardiography (23,31). Similarly, Neuman and colleagues (24) demonstrated that individuals with anemia receiving aged blood (.21 d) had evidence of endothelial dysfunction at 24 hours post-transfusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following single-unit transfusion, other investigators found that intravascular Hb exposure is associated with concomitant elevation in plasma nitrite levels and NO depletion in humans following small volume blood transfusion (Berra et al 2012).…”
Section: Transfusion Of Stored Bloodmentioning
confidence: 99%
“…This binding affinity is so high that Hx "steals" heme from hemoglobin (21). Heme and hemoglobin are synergistic with toll-like receptor (TLR) agonists a more conservative transfusion strategy (1)(2)(3)(4), studies suggesting that older stored blood is associated with higher morbidity than fresh blood (5)(6)(7)(8)(9), studies that older blood has higher levels of cell-free hemoglobin (10,11), in vitro studies in which hemoglobin and heme potentiate release of cytokines from macrophages (12)(13)(14), inTRODUCTiOn There has been increasing appreciation that cell-free plasma hemoglobin and secondarily released free heme may be toxic in critical care settings. Evidence for this concept comes from studies in which liberal transfusion is associated with equivalent or worse outcome than 2 Frank E Riley, perform amidolytic assay: H-D-IIe-ProArg-pNA⋅2HCl (S2288) that is sensitive to a broad spectrum of serine protease, and H-D-Phe-Pip-Arg-pNa⋅2HCl (S2238) that is sensitive to thrombin.…”
mentioning
confidence: 99%